Impact of pharmacist-managed immune checkpoint inhibitor toxicities. (April 2021) - Le, Sonny; Chang, Brandon; Pham, Anthony; Chan, Andrea
Background: Immune checkpoint inhibitors are associated with unique autoimmune side effects that differ from traditional cytotoxic chemotherapy. Pharmacists may play an important role in providing key supportive care measures necessary to aid patients and oncologists through immune-related adverse events (irAEs). This study aims to evaluate the impact of a pharmacist-managed irAE protocol in an oncology clinic. Methods: This study is a retrospective chart review of the implementation of a pilot irAE pharmacy protocol. Patients treated with an immune checkpoint inhibitor and subsequently identified to have dermatologic, gastrointestinal, hepatic, or thyroid toxicities and managed under the pilot irAE pharmacy protocol from 1 October 2018 to 28 February 2019 were enrolled. Study endpoints included number of pharmacist interventions and physician satisfaction. Additional endpoints included pharmacotherapy initiated, dose adjustments, and patient follow-ups. Results: From 1 October 2018, to 28 February 2019, 17 patients were referred and approved by their primary oncologists for pharmacy management under the pilot irAE protocol. During the pilot period, pharmacists initiated 21 new medications for the treatment of irAEs, including thyroid hormone replacement in 7 patients (41%) and oral corticosteroids in 6 patients (35%) with a total of 28 dose adjustments. In addition, the pilot protocol included an assessment of physician satisfaction, which showed a reduced number of physician hours per month managing irAEs, increased physician confidence in irAE management, and a desire for continued pharmacist-management of irAEs. Conclusions: Oncology pharmacists had an impact on management of toxicities in our oncology clinic as indicated by the pharmacist interventions and physician satisfaction.